COST – EFFECTIVENESS ANALYSIS OF USING ANTIDIABETIC IN OUTPATIENT WITH TYPE 2 DIABETES MELLITUS - Siwi Artini, Kusumaningtyas; Ajeng L, Tiara; Wardhani, Annisa Kusuma (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Type 2 diabetes Mellitus is a chronic disease that requires lifelong treatment. In the course of the disease, if blood sugar levels are not controlled, it can lead to complications of other diseases. The variety of antidiabetic drugs used in therapy can lead to differences in the cost effectiveness of therapy. The aims of this study is to analyze the cost-effectiveness of antidiabetic therapy in outpatients at Dr. Moewardi Hospital. Data collection in this study was carried out retrospectively using medical records of outpatients with type 2 diabetes mellitus and billing data from the hospital The data obtained were then presented descriptively and the ACER value was calculated for the 2 most widely used drug groups. The results of this study showed that 30 patients received a combination of Insulin Analog (Basal) + Insulin Analog (Prandial/Premixed) and and 11 patients received Insulin Analog (Basal/ Prandial/ Premixed). The percentage effectiveness of combination therapy Insulin Analog (Basal) + Insulin Analog (Prandial/ Premixed) was higher than Insulin Analog (Basal/ Prandial/ Premixed) (83.33 vs 72.72). The ACER value of Insulin Analog (Basal) + Insulin Analog (Prandial/ Premixed) (IDR 13.802,42) is lower than Insulin Analog (Basal/ Prandial/ Premixed) (IDR 18.356). Based on the cost effectiveness table, the combination of Insulin Analog (Basal) + Insulin Analog (Prandial / Premixed) is more effective so that the combination of Insulin Analog (Basal) + Insulin Analog (Prandial / Premixed) is more cost effective than Insulin Analog (Basal / Prandial / Premixed).